Study on Shear Strengthening of RC Continuous Beams with Different CFRP Wrapping Schemes - Ali, Noorwirdawati; Abdul Samad, Abdul Aziz; Jayaprakash, J.; Iesa, W.M.; Alferjani, M.B.S. (International Journal of Integrated Engineering, 2011)
This paper presents the results of an experimental investigation for enhancing the shearcapacity of reinforced concrete (RC) continuous beams using different CFRP wrappingschemes. A total of five concrete beams were tested and various sheet configurations andlayouts were studied to determine their effects on ultimate shear strength and shear capacity ofthe beams. One beam was kept as control beams, while other beams were strengthened withexternally bonded CFRP strips with four or three sides bonding and one or two layers ofCFRP strips. From the test results, it was found that all schemes were found to be effective inenhancing the shear strength of RC beams. It was observed that the strength increases with thenumber of sheet layers and four sides wrap provided the most effective strengthening for RCcontinuous beam. Beam strengthened using this scheme showed 54% increase in shearcapacity as compared to the control beam. Two prediction models available in literature wereused for computing the contribution of CFRP strips and compared with the experimentalresults.